Talk to us! Communication is a key factor in improving the comfort of MRI research participants. (5th May 2021) - Dewey, Rebecca S.; Ward, Claire; Junor, Andrea; Horobin, Adele
Abstract: Context: Magnetic resonance imaging (MRI) is an invaluable diagnostic and research tool. Having an MRI scan is not always comfortable and may deter people from taking part in MRI research. Maximizing comfort during scanning will improve participants' experiences and image quality. Objective: To define which factors improve comfort during an MRI scan for research by asking people who have participated in MRI research. Setting and participants: People who had participated in MRI research during the past two years were invited, as 'public advisors' to discuss their experiences together and agree on which factors are most important in ensuring comfort while participating in MRI research. Results: Public advisors ranked researcher‐participant communication as the most important factor. In response, an example script to guide MRI researchers in communicating with participants was developed through close consultation between research staff, public advisors and the public. This outlines the often‐missing information necessary to convey to participants, including explaining the reasons behind instructions, managing expectations, providing reassurance, encouragement and progress updates during scanning. Conclusions: Drawing upon personal experiences as MRI research participants, public advisors highlighted the importance of effective and on‐going researcher communication throughout. The example script may be used as a training tool for researchers to help ensure participants' comfort during scanning. Patient and public contribution: All contributors had previously taken part in MRI research. The project was co‐designed, co‐delivered and co‐authored with a public research partner. Public advisors agreed key factors of importance. External public reviewers and public advisors reviewed example script drafts.